The ethnotaxonomic principles of useful indegenous plants of the Mamabolo Community in the Limpopo Province - Mailula, Alice Shaena (University of Limpopo, 2009)
This study contains documentation and naming of indigenous plant species of the GaMamabolo area. Knowledge about their classification and their local natural resources has been acknowledged through this study. It is not only naming and classification but extending information about interaction of useful indigenous plants with human society. This is followed by a survey of 85 plant species found in the Mamabolo area. The immense cultural significance of the traditional knowledge system is portrayed in this study. ii
Thesis (M.A(Folklore)) --University of Limpopo, 2009
Keywords: Ethnotaxonomic principles; Indigenous plants; Indigenous crops; Ethnobotany